2018
DOI: 10.1080/13880209.2018.1428634
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glycyrrhizin on the pharmacokinetics of asiatic acid in rats and its potential mechanism

Abstract: Context: Asiatic acid has been reported to possess a wide range of pharmacological activities.Objective: This study investigates the effects of glycyrrhizin on the pharmacokinetics of asiatic acid in rats and its potential mechanism.Materials and methods: The pharmacokinetics of orally administered asiatic acid (20 mg/kg) with or without glycyrrhizin pretreatment (100 mg/kg/day for seven days) were investigated using a LC–MS method. Additionally, the Caco-2 cell transwell model and rat liver microsome incubati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…There are several studies investigated the effect of GL on the pharmacokinetics of other drugs got similar results. GL decreased the system exposure of asiatic acid by inducing the activity of CYP450 enzymes (Guo et al 2018), and GL increased the clearance rate of paeoniflorin via inducing the activity of CYP3A4 (Sun et al 2019). The co-administration of GL and celastrol could decrease the plasma concentration of celastrol, due to the enhancement GL exerted on the activity of CYP3A4 (Yan et al 2017).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There are several studies investigated the effect of GL on the pharmacokinetics of other drugs got similar results. GL decreased the system exposure of asiatic acid by inducing the activity of CYP450 enzymes (Guo et al 2018), and GL increased the clearance rate of paeoniflorin via inducing the activity of CYP3A4 (Sun et al 2019). The co-administration of GL and celastrol could decrease the plasma concentration of celastrol, due to the enhancement GL exerted on the activity of CYP3A4 (Yan et al 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Next, NBL was orally administered to rats by gavage at a dose of 50 mg/kg. The dosages used in the experiments were based on previous studies (Manthey et al 2011;Guo et al 2018;Sun et al 2019). Blood samples (250 lL) were collected into heparinised tubes via the oculi chorioideae vein at 0.083, 0.33, 0.5, 1, 2, 4, 6, 8, 10, 12 and 24 h after the oral administration of NBL.…”
Section: In Vivo Pharmacokinetic Studymentioning
confidence: 99%
“…Previously, inhibition or induction of cytochrome P450 enzymes (CYP450) was reported to be the main cause responsible for the drug-drug interaction. Especially, the activity of CYP3A4, an enzyme in the liver involved in the metabolism of various drugs, plays vital roles during the pharmacokinetics of several drugs, such as puerarin, warfarin, and asiatic acid, where the inhibition on CYP3A4 resulted in the drug-drug interaction (Guo et al 2018;Liu et al 2019;Song et al 2020). It has been reported that amlodipine is the substrate of CYP3A4, and curcumin has been demonstrated to be an inhibitor of CYP3A4 (Lee et al 2011;Zhu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of CYP450 was mainly related to the metabolic ability of the liver . Several studies showed that glycyrrhizin could regulate the activities of CYP1A2, CYP2D6, CYP2E1, and CYP3A4 . The mRNA expression of CYP1A1, CYP1A2, CYP2C9, CYP2C19, CYP2D6, and CYP2E1 were analyzed by real‐time PCR after HepG2 cells incubated in the hydrogels for 3 days.…”
Section: X‐ray Diffractionmentioning
confidence: 99%
“…40 Several studies showed that glycyrrhizin could regulate the activities of CYP1A2, CYP2D6, CYP2E1, and CYP3A4. [41][42][43] The mRNA expression of CYP1A1, CYP1A2, CYP2C9, CYP2C19, CYP2D6, and CYP2E1 were analyzed by real-time PCR after HepG2 cells incubated in the hydrogels for 3 days. The mRNA expressions of CYP enzymes in each group were showed in Figure 7.…”
Section: Cell Viabilitymentioning
confidence: 99%